An Analysis of Students’ Anxiety in Learning English Speaking Skills at the Tenth Grade Students of SMAN 3 Singaraja - Ni Made Yulinda Dwi Mahayuni (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to describe students' anxiety in speaking English experienced by students of class X at SMAN 3 Singaraja. This study is intended to find the factors that cause anxiety in speaking English and the strategies that students use to overcome this anxiety in speaking. This study used descriptive qualitative method. The data was collected through observation, questionnaires and interviews. The questionnaire was developed by Horwitz and Cope's Foreign Language Classroom Anxiety Scale which the authors adapted from Najiha & Sailun B. which contains 31 items with a 5-point Likert-Scale. The results of this study found that the factors causing anxiety in speaking English experienced by students were ensuring in speaking a foreign language, feeling frightened for not understanding English, nervousness in speaking English, self-consciousness to speak in front of other students, feeling afraid for not understanding the sentences, feeling afraid of making mistakes, getting panicked to speak without preparation, feeling worried about failing English, afraid of being called, thinking other students have better skills, embarrassing to volunteer answers, worried of getting left behind, feeling afraid of being ashamed, fear of overestimation and threatening environment. Meanwhile, the strategies used by students to overcome speaking anxiety are keeping silent, avoiding eye contact, relaxation and control breathing, preparation, focusing on the learning process, and trying or practicing. Students also suggest teachers to create a calm classroom environment and correct students’ mistake to help them overcome their speaking anxiety.